Youth participation in horticulture and poverty reduction in rural areas: A case study of horticultural production in Mvomero district, Tanzania - Gulamiwa, George Nyalulu (Mzumbe university, 2024)
A dissertation submitted at Mzumbe University as a partial fulfillment of the requirements for the award of Master Degree in Development Policy (MSc DP) of Mzumbe University.